The role of vitamin K2 in cognitive impairment: linking vascular health to brain health - Roumeliotis, Stefanos; Kontogiorgos, Ioannis; de Vries, Femke; Maresz, Katarzyna; Jeanne, Jean-François; Leivaditis, Konstantinos; Schurgers, Leon J. (Frontiers in Aging Neuroscience, 2025)
Cognitive impairment, marked by a decline in essential mental aspects such as attention, memory, and problem-solving, is significantly correlated with advancing age. This condition presents a major challenge for the elderly, adversely affecting quality of life, diminishing independence, and imposing substantial burdens on healthcare systems. Recent research indicates that vitamin K2 may be vital for preserving brain health and cognitive function. Traditionally recognized primarily for its role in blood coagulation, vitamin K has emerged in recent years as a nutrient with diverse biological effects essential for healthy aging. A growing body of evidence from both observational and interventional studies underscores the pivotal role of vitamin K2 in mitigating arterial calcification. This mechanism may link vascular health to cognitive function, suggesting that vitamin K2 could play a critical role in the prevention of cognitive impairment in aging populations.